Factors affecting nutrition behavior among middle-class adolescents in urban area of Northern region of Brazil - Eva I. Doyle; Robert H. L. Feldman
INTRODUCTION: Brazil has been called a nation in nutrition transitional because of recent increases in the prevalence of obesity and related chronic diseases. With overweight conditions already prevalent among middle-income populations, there exists a need to identify factors that influence nutrition behavior within this group. OBJECTIVE: To address this subject, a research study was implemented among middle-class adolescents attending a large private secondary school in Manaus, Amazonas, Brazil. The study determined the availability and accessibility of snack foods as well as subjects' attitudes and preferences towards, and the influence of family and friends on healthy (high-nutrient density) snack choices. METHODS: The 4-stage process included: (a) a nutrition expert focus group discussion that reported local nutrition problems in general and factors related to adolescent nutrition, (b) an adolescent pilot survey (n=63) that solicited information about snacking preferences and habits as well as resources for nutrition information and snack money; (c) a survey of various area food market sources to determine the availability and accessibility of high nutrient density snacks; and (d) a follow-up adolescent survey (n=55) that measured snack food preferences and perceptions about their cost and availability. RESULTS: Results included the finding that, although affordable high nutrient density snacks were available, preferences for low nutrient density snacks prevailed. The adolescents were reportedly more likely to be influenced by and obtain nutrition information from family members than friends. CONCLUSION: From study results it is apparent that a focus on food availability will not automatically result in proper nutritional practices among adolescents. This fact and the parental influence detected are evidence of a need to involve adolescents and their parents in nutrition education campaigns to improve adolescent snack food choices.